2x2 - 15x + 14 = 0 ... how?
You need to find the sum of the new roots and the product of the new roots . You should hopefully then know what to do.
Similarly their product is (a+1)(b+1) = ab+a+b+1 = 1/2+11/2+1=7.
Hence the new equation is x^2 - (15/2)x + 7 = 0, and doubling gives 2x^2 - 15x + 14 = 0, as required.
The answer is
x2 + 8x + 216 = 0, I get x2 - 8x + 216 = 0, anyone get why I got (+8x) instead of (-8x) ?
Please read the Guide To Posting at the top of the Maths Forum. Providing full solutions is against the rules. You should just give hints to move people forward in their learning.